1991
DOI: 10.2527/1991.6983308x
|View full text |Cite
|
Sign up to set email alerts
|

Extender and centrifugation effects on the motility patterns of slow-cooled stallion spermatozoa.

Abstract: Slow-cooled stallion spermatozoa, with and without seminal plasma removed by centrifugation, were diluted in Kenney's extender (KE) containing nonfat dry skim milk with glucose and antibiotics or in KE supplemented by adding a modified high-potassium Tyrode's medium (KMT). Four ejaculates from each of four stallions were collected and divided factorially across these four treatments. Percentage of motile sperm, path velocity, and linearity immediately after treatment (0 h) and after storage at 4 degrees C for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(56 citation statements)
references
References 9 publications
0
55
0
1
Order By: Relevance
“…The interaction of extender and centrifugation has been reported in previous studies [17,18] which demonstrate that centrifugation of semen extended with Kenney and a modified (Tyrode-medium) Kenney extender had both negative and positive effects on the motility of cooled semen. In this context, it has been speculated that by adding an extender a beneficial effect is observed through the reduction in concentration of harmful compounds, but that this effect is countered by in the electrolyte balance.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The interaction of extender and centrifugation has been reported in previous studies [17,18] which demonstrate that centrifugation of semen extended with Kenney and a modified (Tyrode-medium) Kenney extender had both negative and positive effects on the motility of cooled semen. In this context, it has been speculated that by adding an extender a beneficial effect is observed through the reduction in concentration of harmful compounds, but that this effect is countered by in the electrolyte balance.…”
Section: Discussionmentioning
confidence: 98%
“…In this context, it has been speculated that by adding an extender a beneficial effect is observed through the reduction in concentration of harmful compounds, but that this effect is countered by in the electrolyte balance. This phenomenon is particularly hard to explain when using extenders composed of natural materials such as skim milk, the content of which is not clearly defined [18]. For optimal protection of cold-stored sperm it is therefore recommended to remove the majority of seminal plasma after centrifugation and to resuspend the sperm pellet with a chemically well defined extender [17].…”
Section: Discussionmentioning
confidence: 99%
“…No differences are seen in sodium or potassium concentrations between ejaculatory fractions (Kareskoski et al 2005). The addition of potassium to semen extenders improves motility of stallion (Padilla and Foote 1991) and human sperm (Karow et al 1992), but Rossato et al (2002) found no correlation between the ionic composition and the osmolarity of human seminal plasma. Intracellular concentrations of potassium are higher than those of seminal plasma, and therefore potassium levels are linked to sperm concentration.…”
Section: Sodium Chloride and Potassiummentioning
confidence: 99%
“…If all seminal plasma is removed, skim milk is not a suitable extender. Addition of a modified high-potassium Tyrode's medium to skim milk extender during cooled storage of ≥24 h in the total absence of seminal plasma has yielded good sperm motility; but if any seminal plasma is left, skim milk alone is better than addition of Tyrode's medium (Padilla and Foote 1991, Webb and Arns 1995, Rigby et al 2001. The effect of seminal plasma during storage may also depend on the temperature; 5°C, room temperature and 40°C have given different results (Wöckener et al 1990, Sieme et al 2001.…”
Section: Role Of Seminal Plasma In Semen Storagementioning
confidence: 99%
See 1 more Smart Citation